Unification of nonclassicality measures in interferometry - Yuan, Xiao (2018)
From an operational perspective, nonclassicality characterizes the exotic behavior in a physical process which cannot be explained with Newtonian physics. There are several widely used measures of nonclassicality, including coherence, discord, and entanglement, each proven to be essential resources in particular situations. There exists evidence of fundamental connections among the three measures. However, the sources of nonclassicality are still regarded differently and such connections are yet to be elucidated. Here, we introduce a general framework of defining a unified nonclassicality with an operational motivation founded on the capability of interferometry. Nonclassicality appears differently as coherence, discord, and entanglement in different scenarios with local measurement, weak basis-independent measurement, and strong basis-independent measurement, respectively. Our results elaborate how these three measures are related and how they can be transformed from each other. Experimental schemes are proposed to test the results.